Cell Wall Polysaccharide-Mediated Cadmium Tolerance Between Two Arabidopsis thaliana Ecotypes - Xiao, Yan; Wu, Xiuwen; Liu, Dong; Yao, Junyue; Liang, Guihong; Song, Haixing; Ismail, Abdelbagi M.; Luo, Jin-Song; Zhang, Zhenhua (Frontiers in Plant Science, 2020)
Cadmium (Cd) is a toxic metal element, and the mechanism(s) underlying Cd tolerance in plants is unclear. Increasingly more studies have been conducted on Cd binding to plant cell walls (CWs), but most of them have focused on Cd fixation by CW pectin, and few studies have examined Cd binding to cellulose and hemicellulose. In this study, We found no difference in Cd uptake in the roots between Arabidopsis ecotype Ph2-23 and Arabidopsis ecotype Tor-1, but higher Cd concentrations were detected in the shoots of Tor-1, and Tor-1 was more tolerant to Cd. When compared to the Ph2-23 cultivar, Cd binding to CW pectin, cellulose, and hemicellulose was significantly higher in the Tor-1 cultivar, as were the concentrations of pectin, cellulose, and hemicellulose. Transcriptome analysis revealed that the genes regulating CW pectin, cellulose, and hemicellulose polysaccharide levels in Tor-1 differed significantly from those in Ph2-23, the expression of most genes such as pectin methyl esterase inhibitors (PMEIs), pectin lyases, xyloglucan endotransglucosylase/hydrolase, expansins (EXPAs), and cellulose hydrolase were higher in Ph2-23, while the expression of cellulose synthase-like glycosyltransferase 3 (CSLG3) and pectin ethyl esterases 4 (PAE4) was higher in Tor-1. Candidate genes were identified that may help regulate CW Cd fixation by polysaccharides. In conclusion, an increase in pectin demethylation activity, a higher content in cellulose and hemicellulose in the Tor-1 cultivar, regulated by related genes, may increase CW retention of Cd and reduce Cd toxicity.